PELATIHAN TOEIC UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA KELAS XII TAV 1 SMK NEGERI 1 SIDOARJO - Risdiana Chandra Dhewy; Endang Lilik Handayani (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
The Test of English for International Communication or abbreviated as TOEIC is an English test for international communication. The purpose of this TOEIC training activity is to improve students' English skills in preparation for the world of work. The participants of this training activity were 15 students of SMK Negeri 1 Sidoarjo class XII majoring in TAV 1. Participants who follow are limited in number because conditions are still in a pandemic situation. So that face-to-face activities must be limited and still adhere to health protocols. The training activities were held in 2 meetings. The first meeting was filled with introduction to TOEIC material and practice questions, for the second meeting filled with ability tests (TOEIC). The activity went smoothly and students participated in the activity enthusiastically. Based on the results of student tests, the results showed that the highest TOEIC score was 455 and the lowest score was 375. The average score of the 15 samples was 421 with 12 students scoring above the minimum limit in general and 3 students still below the minimum limit. The minimum limit for the TOEIC score in general is 405. Students can be even more enthusiastic about learning English in order to improve their English skills in dealing with the world of work.